Humid Summers Promote Urban Aqueous‐Phase Production of Oxygenated Organic Aerosol in the Northeastern United States - Mitchell J. Rogers; Taekyu Joo; Tori Hass‐Mitchell; Manjula R. Canagaratna; Pedro Campuzano‐Jost; Donna Sueper; Mia N. Tran; Jo E. Machesky; Joseph R. Roscioli; Jose L. Jimenez; Jordan E. Krechmer; Andrew T. Lambe; et al. (Geophysical Research Letters)
Abstract Aqueous‐phase uptake and processing of water‐soluble organic compounds can promote secondary organic aerosol (SOA) production. We evaluated the contributions of aqueous‐phase chemistry to summertime urban SOA at two sites in New York City. The relative role of aqueous‐phase processing varied with chemical and environmental conditions, with evident daytime SOA enhancements (e.g., >1 μg/m3) during periods with relative humidities (RH) exceeding 65% and often higher temperatures. Oxygenated organic aerosol (OOA) production was also sensitive to secondary inorganic aerosols, in part through their influence on aerosol liquid water. On average, high‐RH periods exhibited a 69% increase in less‐oxidized OOA production in Queens, NY. These enhancements coincided with southerly backward trajectories and greater inorganic aerosol concentrations, yet showed substantial intra‐city variability between Queens and Manhattan. The observed aqueous‐phase SOA production, even with historically low sulfate and nitrate aerosol loadings, highlights both opportunities and challenges for continued reductions in summertime PM2.5 in urban communities.